Simpatectomia lombar retroperitoneal endoscópica - Loureiro,Marcelo de Paula (2004)
In the last few years, there has been an increase in the indication of lumbar sympathectomy for plantar hyperhidroses. There are few reports of the laparoscopic access for this operation, even when it seems to be a very apropriate method. A case of a left lumbar sympathectomy through the retroperitoneal endoscopic approach is presented. The total control of left plantar hiperhidroses was achieved, showing the effectiveness of this operation, completely feasible through extraperitoneal endoscopic route.